Interleukin-1β induces sleep independent of prostaglandin D2 in rats and mice. (6th January 2017) - Zhang, Bin-Jia; Shao, Shu-Rong; Aritake, Kosuke; Takeuchi, Atsuko; Urade, Yoshihiro; Huang, Zhi-Li; Lazarus, Michael; Qu, Wei-Min
Highlights: We studied whether IL-1β-induced sleep is mediated by prostaglandins. IL-1β induces sleep in rats and mice with or without COX-2 inhibitor treatment. IL-1β induces sleep in PGD2 receptor subtype DP1 KO mice. IL-1β induced sleep is independent of PGD2 and other COX-2-derived prostaglandins. Abstract: Interleukin-1β (IL-1β) and prostaglandin (PG) D2 are endogenous sleep-promoting substances. Since it was reported that a highly selective cyclooxygenase-2 (COX-2) inhibitor, NS398, completely inhibited IL-1β-induced sleep in rats, IL-1β-induced sleep had been believed to be mediated by prostanoids, most probably PGD2 . However, in the present study, pretreatment of rats with NS398 (3 mg/kg) did not suppress the 64.2% increased non-rapid eye movement (non-REM, NREM) sleep during infusion of IL-1β (10 ng) for 6 h in the nocturnal (active) period between 23:00 and 5:00 into the subarachnoid space of the PGD2 -sensitive sleep-promoting zone of the basal forebrain. Meanwhile, IL-1β at doses of 1.7 and 5 μg/kg also significantly increased NREM sleep for 6 h after intraperitoneal injection at 20:00 (light-off time) by 76.8% and 121.1%, respectively, in wild-type (WT) mice, by 67.7% and 147.3%, respectively, in WT mice pretreated with NS398 (5 mg/kg) and by 108.9% and 121.6%, respectively, in PGD2 receptor (DP1 R) knockout mice. These results indicate that IL-1β-induced NREM sleep is independent of the PGD2 /DP1 R system and other COX-2-derived prostaglandins in rats and mice.